1994
DOI: 10.1111/j.1365-2427.1994.tb01152.x
|View full text |Cite
|
Sign up to set email alerts
|

International collaboration in freshwater ecology

Abstract: I 1. International collaboration in freshwater ecology was examined using authorship affiliations of articles published in thirty-three spedalized journals. Most are published in Europe. 2. Researchers from four to thirty-seven different countries were represented in the 100 articles examined for each journal. Only 29% of articles were single-authored; multicountry authors' addresses (indicating international collaboration) were found for 9% (range 0-23% per journal) of articles examined. 3. Five of the eighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 8 publications
2
26
1
Order By: Relevance
“…Then bibliometric studies on more narrow environmental fields are reviewed, including all published articles that we could identify (WAGNER, 2005;ENGELS et al, 2005;DASTIDAR, 2004;WISHART & DAVIS, 1998;RESH & YAMAMOTO, 1994). There are some limitations with regard to the statistical sources, as the most recent data published by NSB on worldwide fieldspecific internationalisation cover the period 1995-1997(NSB, 2000.…”
Section: International Collaboration In Ees Fields: Review Of Statistmentioning
confidence: 99%
See 1 more Smart Citation
“…Then bibliometric studies on more narrow environmental fields are reviewed, including all published articles that we could identify (WAGNER, 2005;ENGELS et al, 2005;DASTIDAR, 2004;WISHART & DAVIS, 1998;RESH & YAMAMOTO, 1994). There are some limitations with regard to the statistical sources, as the most recent data published by NSB on worldwide fieldspecific internationalisation cover the period 1995-1997(NSB, 2000.…”
Section: International Collaboration In Ees Fields: Review Of Statistmentioning
confidence: 99%
“…Nevertheless, Wagner's attempt underlines the need for a better qualitative understanding of EES fields to explain internationalisation patterns. RESH & YAMAMOTO (1994) carefully select specialised journals and report collaboration frequencies per journal. Their conclusion that internationalisation in Freshwater Ecology approximates that of Physics does not seem well-founded because it disregards a time lag of almost a decade between investigated periods.…”
Section: International Collaboration In Ees Fields: Review Of Statistmentioning
confidence: 99%
“…Cooley and Golley (1984) showed that Canada ranked third among all nations in 1982, slightly behind the USSR and slightly in front of Great Britain, in the number of ecological authors. A survey of 3300 articles published in 33 freshwater journals since 1985 (Resh and Yamamoto 1994) showed Canada to be the second-most productive nation in that area, producing a third as many papers as the first-ranked U.S.A. (i.e., three times as many per capita).…”
Section: Discussionmentioning
confidence: 99%
“…The situation does not seem encouraging. Although international collaboration in limnology is higher than in many other fields of science (RESH and YAMAMOTO, 1994), present collaborations and technology transfers from the first to the third world are still inadequate and do not lead to capacity building in third world countries (WISHART and DAVIES, 1998). On the other hand, some of the developing countries were economically most successful in the last decade and it may no longer be Publications of BRIC-and Outreach Countries 299…”
mentioning
confidence: 99%